ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL URAIAN PADA MATERI BANGUN RUANG SISI DATAR - Fahlevi, Muhamad Syahreza; Zanthy, Luvy Sylviana (IKIP Siliwangi, 2020)
This study aims to determine the difficulty of students in solving the problem description on the material to build a flat sided space. Indicators of difficulty in research are difficulties in understanding concepts, difficulties in applying principles and difficulties in skills. This research method using qualitative descriptive method. This research is conducted in SMP Negeri 1 Cihampelas in Grade VIII of academic year 2019-2020. The population of this study was all eighth grade junior high school students in West Bandung Regency. The subject of the research is the students of class VIII-10, namely students who have high mathematical abilities, moderate mathematical abilities, and low mathematics. To obtain research data an instrument was used in the form of test item description. The results of this study prove that subjects with high mathematical ability are able to apply principles and are skilled in solving problems, but still have difficulty understanding concepts and mathematical abilities are already able to understand concepts but in applying principles are still having difficulties and also experiencing skills difficulties, whereas low mathematically capable subjects have not been able to apply concepts and in applying principles are also still experiencing difficulties and experiencing difficulty in skills.